The Implication of Neuroactive Steroids in Tourette's Syndrome Pathogenesis: A Role for 5α‐Reductase?. (28th October 2013) - Bortolato, M.; Frau, R.; Godar, S. C.; Mosher, L. J.; Paba, S.; Marrosu, F.; Devoto, P.
Abstract : Tourette's syndrome (TS) is a neurodevelopmental disorder characterised by recurring motor and phonic tics. The pathogenesis of TS is considered to reflect dysregulations in the signalling of dopamine (DA) and other neurotransmitters, which lead to excitation/inhibition imbalances in cortico‐striato‐thalamocortical circuits. The causes of these deficits may reflect complex gene × environment × sex (G × E × S) interactions; indeed, the disorder is markedly predominant in males, with a male‐to‐female prevalence ratio of approximately 4 : 1. Converging lines of evidence point to neuroactive steroids as being likely molecular candidates to account for G × E × S interactions in TS. Building on these premises, our group has begun examining the possibility that alterations in the steroid biosynthetic process may be directly implicated in TS pathophysiology; in particular, our research has focused on 5α‐reductase (5αR), the enzyme catalysing the key rate‐limiting step in the synthesis of pregnane and androstane neurosteroids. In clinical and preclinical studies, we found that 5αR inhibitors exerted marked anti‐DAergic and tic‐suppressing properties, suggesting a central role for this enzyme in TS pathogenesis. Based on these data, we hypothesise that enhancements in 5αR activity in early developmental stages may lead to an inappropriate activation of the 'backdoor' pathway for androgen synthesis from adrenarche until the end of puberty. We predict that the ensuing imbalances in steroid homeostasis may impair the signalling of DA and other neurotransmitters, ultimately resulting in the facilitation of tics and other behavioural abnormalities in TS.